CHI3L1 in the CSF is a potential biomarker for anti-leucine-rich glioma inactivated 1 encephalitis - Li, Jinyi; Li, Hongyan; Wang, Yunhuan; Zhao, Xiuhe; Wang, Shengjun; Li, Ling (Frontiers in Immunology, 2023)
Objective: Anti-leucine-rich glioma inactivated 1(LGI1) encephalitis is one rare autoimmune encephalitis which is accompanied by inflammatory responses. This study aimed to investigate the Chitinase 3-like 1(CHI3L1)in anti-LGI1encephalitis patients and evaluate its association with modified Rankin Scale (mRS) score in anti-LGI1 encephalitis at admission and 6 months follow-up. Methods: Thirty-five patients with anti-LGI1 encephalitis and 22 patients with non-inflammatory neurological disease were enrolled in this study. Cerebrospinal fluid (CSF) and serum levels of CHI3L1 were measured by enzyme-linked immunosorbent assay. Patients were evaluated for mRS score at admission and at 6 months follow-up. Results: CHI3L1 levels in CSF and serum were highly elevated in patients with anti-LGI1 encephalitis at admission compared those with the controls. The level of CSF CHI3L1 was correlated with mRS score both at admission and the 6 months follow-up. CHI3L1 level in CSF was also positively correlated with CSF lactate level. However, serum CHI3L1 level was not correlated with mRS score and other clinical features. The mRS score of patients at admission positively associated with hyponatremia and negatively associated with FBDS. Conclusion: CHI3L1 level in CSF is correlated with the severity and prognosis of anti-LGI1 encephalitis.